Aesthetic Sensibility - Arnold Berleant (Ambiances)
Aesthetics is fundamentally a theory of sensible experience. Its scope has expanded greatly from centering on the arts and scenic nature to the full range of appreciative experience. Expanding the range of aesthetics raises challenging questions about the experience of appreciation. Traditional accounts are inadequate to identify and illuminate the perceptual experiences that these new applications evoke. Considering the range of environmental and everyday occasions aesthetically changes aesthetics into a descriptive and not necessarily celebratory study of sensible experience, for it must now accommodate a complete range of negative as well as positive values.